2017
DOI: 10.1051/0004-6361/201629155
|View full text |Cite
|
Sign up to set email alerts
|

The ALMA Redshift 4 Survey (AR4S)

Abstract: We introduce the ALMA Redshift 4 Survey (AR4S), a systematic ALMA survey of all the known galaxies with stellar mass (M * ) larger than 5 × 10 10 M at 3.5 < z < 4.7 in the GOODS-south, UDS and COSMOS CANDELS fields. The sample we have analyzed in this paper is composed of 96 galaxies observed with ALMA at 890 µm (180 µm rest-frame) with an on-source integration time of 1.3 min per galaxy. We detected 32% of the sample at more than 3σ significance. Using the stacked ALMA and Herschel photometry, we derived an a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

18
114
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(132 citation statements)
references
References 57 publications
18
114
0
Order By: Relevance
“…This result provides further theoretical support to the recent claim by Gavazzi et al (2015a) that bars are one of the main contributor of the flattening observed at high masses in the star formation rate-stellar mass correlation (Whitaker et al 2012;Magnelli et al 2014;Whitaker et al 2014;Gavazzi et al 2015b;Ilbert et al 2015;Lee et al 2015;Schreiber et al 2016).…”
Section: Discussionsupporting
confidence: 88%
“…This result provides further theoretical support to the recent claim by Gavazzi et al (2015a) that bars are one of the main contributor of the flattening observed at high masses in the star formation rate-stellar mass correlation (Whitaker et al 2012;Magnelli et al 2014;Whitaker et al 2014;Gavazzi et al 2015b;Ilbert et al 2015;Lee et al 2015;Schreiber et al 2016).…”
Section: Discussionsupporting
confidence: 88%
“…Such temperatures are very similar to the 40±2 K found for a massive sample of z∼4 galaxies by Schreiber et al (2016) and the 40-50 K found by Sklias et al (2014) for typical z∼2-3 sources from the Herschel Lens Survey (Egami et al 2010). We remark that one might naturally expect an evolution in dust temperature given the observed evolution in the SFR surface densities observed in galaxies with cosmic time (e.g., Shibuya et al 2015) and the correlation of dust temperature with SFR surface density (e.g., Elbaz et al 2011).…”
Section: Impact Of the Dust Temperaturesupporting
confidence: 85%
“…11 M e galaxies at z>1 in our sample, show strong AGN or starburst activity, which is also seen in other samples of massive high-z galaxies (Spitler et al 2014;Martis et al 2016;Schreiber et al 2017). Also, as expected, the Herschel galaxies fall on the red side of the starforming population, and the radio galaxy (ES1C_55) plots among the quiescent objects.…”
Section: Discussionsupporting
confidence: 86%